Legal Protection Policy For Witnesses in The Criminal Jurisdiction Process - Hadi Supriyanto (Research institutions and community service Universitas Muhammadiyah Buton, 2020)
In writing this scientific paper, the main focus is how a criminal justice process in effect in Indonesia, as regulated in the Criminal Procedure Code (CPC) has accommodated witness protection issues. The birth of the Witness Protection Law, as well as the author's observations on the criminal court process, have become concepts of thinking about the importance and need for witness protection in the criminal justice process. The problems in this scientific paper are how the legal formulation of witness protection in the criminal justice process, how the implementation of legal protection policies for witnesses in the criminal justice process, and how the legal formulation policies regarding witness protection in the criminal justice process in the future. On the basis of these observations, research was carried out by selecting the type of descriptive analytical research. The formulation of the witness protection law is a phenomenon of Indonesian criminal procedural law as a sub-system of criminal justice, where enforcement always intersects with law enforcers. In enforcing the law in the protection of witnesses, it was found that witnesses often did not receive legal protection and were even made suspects. Thus in the policy formulation of law regarding witness protection in the future, it is necessary to harmonize the law, both the Criminal Code, the Criminal Procedure Code which is formed in one legal system, so as to facilitate the implementation of the law. The witness and victim protection law is the nation's newest work in the development of Indonesian criminal law which has inspired a legal ideal that protects all human rights. the Indonesian nation, especially the rights of witnesses and victims in the criminal justice process. Thus witness protection law is a guideline in formulating criminal law in a standard legal system, namely in a legal formulation of the Indonesian criminal justice system.